Ni hao Mr. Pérez, buenos días Mr. Li : Chile y China: cultura, negocios y confianza en la era global - Labarca, Claudia (Ediciones UC, 2015)
This work aims to revalue, through an emblematic case study for the internationalization and economic development of Chile - trade relations with the People's Republic of China - the idea that in intercultural business links there are considerations that cannot be ignored. side, beyond the market. Communication, the development of bonds of trust, as well as other adaptation mechanisms are essential for success in business. Based on more than 90 interviews with actors in the bilateral relationship carried out in Shanghai, Beijing and Santiago de Chile, the dimensions of an intercultural commercial relationship, such as the one between the PRC and Chile, are addressed from the voice of the participants themselves. A case study that shows that the business of doing business cannot be seen from reductionist perspectives, but must be analyzed from a broad and diverse perspective.